1987
DOI: 10.2527/jas1987.6461655x
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Digestibility of Amino Acids, Gross Energy and Starch in Corn, Sorghum, Wheat, Barley, Oat Groats and Wheat Middlings for Growing Pigs

Abstract: Apparent nutrient digestibilities of yellow-dent corn, low-tannin sorghum, hard red winter wheat, barley, oat groats and wheat middlings were determined near the end of the small intestine and over the total digestive tract of growing pigs. Gross energy digestibilities for corn, sorghum and oat groats were similar; wheat had a slightly lower (P less than .05) digestibility, followed by barley (P less than .05), with wheat middlings being the least (P less than .05) digestible. About 7% of the gross energy in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
4
6

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 15 publications
(21 reference statements)
7
34
4
6
Order By: Relevance
“…In the case of arginine, Charlton et al (2002) reported that this AA strengthens the interaction between proteins and tannins forming an additional site of interaction. The CIAD of protein and AA from S in growing pigs are in the range of values reported previously (Lin et al, 1987;Mariscal-Landín, 1992;Mariscal-Landín et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…In the case of arginine, Charlton et al (2002) reported that this AA strengthens the interaction between proteins and tannins forming an additional site of interaction. The CIAD of protein and AA from S in growing pigs are in the range of values reported previously (Lin et al, 1987;Mariscal-Landín, 1992;Mariscal-Landín et al, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…O valor referente à composição da lisina no milheto (0,50%) foi 44% superior ao valor de 0,35% apresentado por Rostagno et al (2000). (Lin et al, 1987).…”
Section: Resultsunclassified
“…The database A database containing AID of CP and AA in 38 barley samples for pigs was extracted from a total of 26 peer-reviewed papers with data on AID of CP and AA in barley including studies of Baidoo and Liu (1998) (3);De Lange et al (1990) (1); Fan et al (1993) (1); Fan and Sauer (1995) (1); Fan and Sauer (2002) (6); Fernández-Fígares et al (2008) (1) ;Fuller et al (1994) (1); Furuya and Kaji (1991) (1); Green et al (1987) (1); Ige et al (2010) (2); Jørgensen et al (1997) (2); Lin et al (1987) (1); Nitrayová et al (2006) (1); Nyachoti et al (1997) (1); Pedersen et al (2007) (1); Perttilä et al (2002) (1); Reverter and Lindberg (1998) (1); Rowan and Lawrence (1986) (1); Sauer et al (1977) (1); Sauer et al (1981) (4); Schröder et al (1989) (1); Stein et al (1999) (1); Taverner et al (1981b) (1); Yin et al (1993) (1); Yin et al (2001a) (1) and Yin et al (2002) (1) (number of barley samples per study is given in brackets). The selection of these peer-reviewed papers was based on several criteria including (1) complete information on diet composition; (2) complete information on CP and AA contents of the diet and (or) barley; (3) use of barley as the only source of protein in the diet; (4) diets being devoid of feed additives.…”
Section: Methodsmentioning
confidence: 99%